Mobile cloud computing: a review on smartphone augmentation approaches - Abolfazli, S.; Sanaei, Z.; Gani, Abdullah (2012)
Smartphones have recently gained significant popularity in heavy mobile processing while users are increasing their expectations toward rich computing experience. However, resource limitations and current mobile computing advancements hinder this vision. Therefore, resource-intensive application execution remains a challenging task in mobile computing that necessitates device augmentation. In this article, smartphone augmentation approaches are reviewed and classified in two main groups, namely hardware and software. Generating high-end hardware is a subset of hardware augmentation approaches, whereas conserving local resource and reducing resource requirements approaches are grouped under software augmentation methods. Our study advocates that consreving smartphones' native resources, which is mainly done via task offloading, is more appropriate for already-developed applications than new ones because of costly re-development process. Moreover, cloud computing is one of the major cornerstone technologies in augmenting computing capabilities of smartphones. Sample execution model for intensive mobile applications is presented and taxonomy of augmentation approaches is devised. For better comprehension, the results of this study are summarized in a table.